Application of Indonesian National Standard (SNI) on Helmets of Two-Wheeled Motor Vehicle Riders: Consumer Rights and Obligations of Business Actors - Lumban Gaol, Christopher Panal (Journal of Progressive Law and Legal Studies, 2023)
This paper discusses the application of the Indonesian National Standard (SNI) on two-wheeled motorized vehicle helmets and its implications for consumer rights and obligations of business actors. Based on the Regulation of the Minister of Industry of the Republic of Indonesia Number: 79/M-IND/PER/9/2015, SNI for helmets of two-wheeled motorized vehicle riders is compulsorily enforced. Business actors who produce and/or import helmets must meet SNI requirements and have a product certificate using the SNI mark installed on the product. Consumers have rights protected by the Consumer Protection Law, including the right to comfort, security, and safety in consuming goods and/or services. They have the right to true, clear and honest information about helmet products, and have the right to raise opinions and complaints. If the helmet product does not comply with the agreement, the consumer is entitled to compensation and compensation. On the other hand, business actors have an obligation to provide true, clear, and honest information about the condition and guarantee of helmet products. They must treat consumers properly and honestly, as well as provide compensation, indemnity and replacement if the helmet product does not comply with the agreement. The Indonesian National Standard (SNI) for helmets of two-wheeled motorized vehicle riders, such as Helm SNI 1911:2007, specifies technical requirements related to materials, designs, and features that must be met by helmets. These requirements include materials that are strong, do not change by temperature changes, and do not cause irritation to the skin. The helmet design must also meet certain criteria, including height, ventilation, and bearing. Full face helmets and open face helmets have different technical requirements, such as ear protection, neck covers, shields, or chin caps for full face helmets, and hoods, protective linings, straps and more for open face helmets.In conclusion, this paper underlines the importance of applying SNI to two-wheeled motorized vehicle helmets to maintain product quality, safety, and comfort. Consumers have rights that must be protected, while business actors have the obligation to meet SNI requirements and provide good service to consumers. With SNI, it is hoped that two-wheeled motorized vehicle helmets on the market can meet the standards that have been set, so as to provide better protection for riders.